Using Soft Systems Methodology (SSM) in Formulating Knowledge Management Systems (KMS) Strategy for Malaysian Public Institutions of Higher Education (PIHE) - Md. Saad, Nor Hasliza; Alias, Rose Alinda; Abdul Rahman, Azizah (2006)
The purpose of this paper is to discuss both the methodology and the finding on how Soft Systems Methodology (SSM) is used as a basis for formulating KMS strategy in four case studies conducted within Malaysian Public Institution of Higher Education (PIHE) context. The concept of SSM was used to integrate two streams of cultural analysis and logic-based analysis to understand the ill-structured problem situation in the context. Throughout the analysis Multiple Perspectives (MP) Theory by Mitroff and Linstone (1993) is employed to differentiate between the Technical Perspective, Organizational Perspective and Personal Perspective of the formulation of KMS strategy in the context. This approach presents a holistic view of formulating KMS strategy by combining both technical and non-technical issues including business processes and human activities within an organization. The processes reflect upon the objective to answer the two main research questions; (a) How to formulate a holistic strategy for KMS implementation? and (b) What are the factors influencing the formulation of KMS strategy?